Development of alternative concrete bridge superstructure systems for short and medium span bridges. (15th July 2017) - Menkulasi, Fatmir; Kuruppuarachchi, Dinesha
Highlights: Two concrete bridge superstructure systems (PS2 and PS4) are presented. PS2 is lighter than the box beam system and features shallower depths. PS2 also requires fewer strands and generally exhibits lower camber. PS4 features shallower depths compared to the decked bulb tee system. PS4 also exhibits lower live load deflections and camber. Abstract: Two new concrete bridge superstructure systems for short and medium span bridges are presented. The investigated systems consist of adjacent hollow precast concrete beams with and without concrete topping. The proposed configurations are compared with traditional adjacent box beam and decked bulb tee systems for spans that range from 24.4 m to 45.7 m. It is demonstrated that the proposed system that features concrete topping (PS2) is lighter than the adjacent box beam system, requires fewer strands, provides shallower superstructure depths, and exhibits lower cambers for spans equal to 24.4 m and 30.5 m. PS2 addresses the reflective cracking problems manifested in adjacent box beam systems by shifting the location of the longitudinal connections to the bottom flange and away from traffic loads. The system that features no topping (PS4) is slightly heavier than the decked bulb tee system, but features shallower superstructure depths, requires fewer strands, and exhibits lower live load deflections and camber. Transverse bending moments demand in PS4 are reduced compared to the decked bulb tee system due to the smaller span provided by the two web supports. Live load distribution factors (LLDF) for PS2 and PS4 can be conservatively estimated using AASHTO provisions for adjacent box and decked bulb tee systems, respectively.